(untitled) (Medical Forum Monthly, 2025)
Objective: To study Independent Influence of Sleep Quality, Daytime Sleepiness, and Chronotype on Mental Health and Academic Performance among MBBS Students Mirpur AJK Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department Of Community Medicine & Medical Education of MBBS Medical College, Mirpur AJK from 1st March 2024 to 30th February, 2025. Methods: Data were comprehensively collected through a validated questionnaire, which included the Pittsburgh Sleep Quality Index (PSQI) to accurately assess sleep quality, the Epworth Sleepiness Scale (ESS) to objectively evaluate daytime sleepiness, the Depression Anxiety Stress Scale (DASS-21) to precisely determine mental health status, and the Morningness–Eveningness Questionnaire (MEQ) to reliably identify chronotype. Academic performance was objectively measured using Grade Point Average (GPA). Statistical analysis was meticulously performed using SPSS version 21.0, and significance was appropriately set at p < 0.05. Result: Among 200 medical students, poor sleep quality was negatively associatively linked with academic performance, as those with poor sleep academically worse performed (mean GPA 2.93 ± 0.34) compared to goodsleepers (3.44 ± 0.27). Daytime sleepiness adversely associatively reduced GPA, progressively declining from normal alertness (3.38 ± 0.31) to moderate-to-severe sleepiness (2.78 ± 0.36). Mental health was statisticallysignificantly influenced by sleep quality, with poor sleepers more frequently reporting distress (p < 0.001). Chronotype correlatively varied, as morning types academically better performed (3.45 ± 0.28), while evening typesacademically worse performed (2.82 ± 0.35). Regression analysis independently demonstratively confirmed that poor sleep quality and higher daytime sleepiness negatively predictively and adversely associatively influenced GPA, collectively showing that disturbed sleep physiology strongly impactfully affected both academic performanceand mental health. Conclusion: Overall, reduced sleep quality, increased sleepiness, and late chronotype were negatively and substantially associated with academic success and mental wellness. Therefore, it is strongly suggested that healthy sleep habits and regular sleep schedules,